PENINGKATAN KUALITAS PEMBELAJARAN PENJUMLAHAN DAN PENGURANGAN PECAHAN MELALUI PENDEKATAN MATEMATIKA REALISTIK BERBANTUAN KERTAS ORIGAMI SISWA KELAS IV SDN 08 SAGULUBBEK - Jonas (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2022)
Research problems include the lack of student learning outcomes. Only 55.89% of students met the KKM in the discussion of the material regarding addition and subtraction of fractions with an average value of 70. The purpose of this study was to increase the quality of learning addition and subtraction of fractions in fourth grade students of SDN 08 Sagulubbek by carrying out a realistic mathematical approach using origami paper. The research was held covering the stages of planning, taking action, observing, and reflecting. The subjects of this study were fourth graders at SDN 08 Sagulubbek, with a total of 34 students, 22 boys and 12 girls. The data obtained include quantitative and qualitative data using test and non-test techniques. From the implementation of the first cycle obtained a value of 78.26 (B). In cycle II, the value increased to 87.97 (A). In the first cycle, the percentage of student learning activities was up to 68.35% and in the second cycle it rose to 82.9%. In the first cycle, the average value of student learning outcomes touched 82.89 with a classical completion percentage of 85.29%. Meanwhile, in the second cycle, the average value of the students' learning outcomes rose to 90.46 with the percentage of completing classical learning of 91.18%. From the final results of this study, it can be concluded that the choice of applying a realistic mathematical approach using origami paper can increase the quality of teaching and learning from adding and subtracting fractions for fourth grade students at SDN 08 Sagulubbek for the 2018/2019 school year.